Long term follow-up of hyperimmunoglobulin M syndrome cases - (:unkn) unknown (My University, 2010)
Giriş: Hiperimmünglobulin M (HIGM) sendromu normal ya da yüksek serum IgM düzeylerinin varlığında diğer immünglobulin seviyelerinin düşüklüğü ile seyreden primer bir immünyetmezlik hastalığıdır. Son yıllarda bu hastalığın moleküler ve genetik temellerine ilişkin gelişmeler kaydedilmekte olup beş alt grup olarak tanımlanmıştır. Gereç ve Yöntem: Kliniğimizde HIGM tanısı ile takip edilen hastalar demografik ve klinik özellikleri, tanı yaşı, aile öyküsü ve laboratuvar bulguları açısından retrospektif olarak değerlendirilmiştir. Olguların tam kan sayımları, periferik yayma incelemeleri, serum immünglobulin düzeyleri, lenfosit alt grup incelemeleri, CD40 ve sağlıklı kontrollere göre uyarılmış CD40 ligand (CD40L) gösterimleri çalışılmıştır. Bulgular: Bu çalışmada 5 HIGM (4 erkek, 1 kız) olgusunun ortalama 7.2 yıl (median: 9, min-maks: 0.4-11.6 yıl) süreyle izlemi değerlendirilmektedir. Hastaların şikayetleri genellikle süt çocukluğu döneminde başlarken tanı yaşı 1.3-2.3 yıl (median: 2 yıl) arasında değişkenlik göstermekteydi. Dört ailede eş akrabalığı bulunmaktaydı. Bu sendroma eşlik edebilen otoimmünite, lenfoma, nötropeni ve ektodermal displazi tabloları hiçbir olgumuzda saptanmamıştır. CD40 gösterimi dört olguda çalışılmış ve normal düzeylerde saptanmıştır. Bu olgularda uyarılmış CD40L gösterimi ise sadece kız olguda saptanırken, diğer üç erkek olguda gösterilememiştir. Akciğer görüntülemesinde bronşektazi üç olguda gözlenmiştir. Tüm olguların takibinde intravenöz immünglobulin tedavisi ve antibiyotik profilaksisi kullanılmaktaydı. Sonuç: HIGM sendromlu olgular sık infeksiyon geçirme ve kalıcı akciğer hasarı oluşması riskleriyle karşılaşmaktadır. Bunlardan korunmak için erken yaşta tanı konulması ve tedaviye bir an önce başlanması oldukça önem taşımaktadır.

Objective: Hyperimmunoglobulin M (HIGM) syndromes are primary immunodeficiencies characterized by normal or elevated serum IgM levels with decreased levels of other immunoglobulin isotypes. Over the past decade rapid progress has been made in the molecular and genetic basis of HIGM and five distinct subgroups have been described. Materials and Methods: Records of patients diagnosed as HIGM were retrospectively reviewed to describe the demographic characteristics, initial clinical presentation, age at onset and diagnosis and family history of immunodeficiency, in addition to basic immunological laboratory parameters, and information about follow-up and outcome of patients. Laboratory analyses included complete blood cell and differentials, serum immunoglobulin levels and immunophenotyping of peripheral blood lymphocytes. Flow cytometric analyses of CD40 and stimulated CD40 ligand (CD40L) expression were performed and compared to healthy controls. Results: We hereby describe 5 HIGM cases (1 female, 4 male) followed in our unit with a mean duration of 7.2 (median 9 years; min-max: 0.4-11.6) years. The age at diagnosis ranged between 1.3-2.3 years (median 2 years), whereas onset of symptoms was generally during infancy. Four cases were from consanguineous parents. Neither autoimmunity, lymphoma, neutropenia or ectodermal dysplasia were detected in any of cases. Evaluation of CD40 was available in four cases and showed normal expression. Stimulated CD40L expressions were found to be normal in the girl and remarkably lower than healthy controls in three boys. Lung imaging revealed bronchiectasis in three patients. All patients are under intravenous immunoglobulin treatment and antibiotic prophylaxis. Conclusion: HIGM is associated with an increased risk of severe infections and chronic lung damage. Early-diagnosis and prompt initiation of intravenous immunoglobulin therapy is essential to prevent complications.
Hiperimmünglobulin M sendromlu olguların uzun dönem izlemi
Keywords: İmmünoloji